2016
DOI: 10.1055/s-0036-1584192
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Total Knee Replacement via Two Approaches in Indian Scenario

Abstract: This study was designed to assess the early and late clinical and functional outcome based on Knee Society Score in patients undergoing total knee replacement (TKR) by medial parapatellar approach/midvastus approach. A total of 52 patients were included in the study of whom 28 patients were operated by medial parapatellar approach and 24 by midvastus approach. Patients were assessed on the basis of Knee Society Score, along with other parameters such as duration of hospital stay, blood loss during, and after s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 13 publications
2
6
0
Order By: Relevance
“…The stated surgical reason for early return of full SLR is due to the fewer lateral retinacular releases involved in midvastus approach 11 . This finding is in accordance with studies 1,4 that mid-vastus is advantageous over the standard procedure in the early postoperative period. The key finding of significant improvements in isometric quadriceps muscle strength at POST 1 and at three months, further substantiates that mid-vastus is a muscle sparing approach in TKR procedure.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The stated surgical reason for early return of full SLR is due to the fewer lateral retinacular releases involved in midvastus approach 11 . This finding is in accordance with studies 1,4 that mid-vastus is advantageous over the standard procedure in the early postoperative period. The key finding of significant improvements in isometric quadriceps muscle strength at POST 1 and at three months, further substantiates that mid-vastus is a muscle sparing approach in TKR procedure.…”
Section: Discussionsupporting
confidence: 93%
“…Studies 3-4 concluded that the functional outcome as well as functional recovery of muscle strength and post-operative pain were noted to be better in mid-vastus than medial parapatellar approach. These studies have mostly analysed the functional outcome in comparing approaches on a surgical perspective rather on post-operative therapeutic interventions.…”
Section: Introductionmentioning
confidence: 99%
“…[ 3 ] In addition, better surgical outcomes with traditional protocols in short-term reports in favor of minimal invasive approaches also encouraged rapid recovery protocol builders to prefer minimal invasive approaches. [ 3 , 4 , 6 , 7 ] However, these recommendations are not evidence based and, to our knowledge, there is no study comparing surgical outcomes between minimal invasive approaches and MPP approach in terms of pain, LOS and functional recovery in fast-track TKA patients. [ 8 - 12 ] In addition, Enhanced Recovery After Surgery (ERAS®) Society declared a consensus statement at the beginning of 2020 about perioperative care in total hip arthroplasty (THA) and TKA, and recommended that more evidence is needed to prefer one type of surgical approach over another in terms of the use of a minimally invasive technique with an ERAS® set up.…”
Section: Introductionmentioning
confidence: 99%
“…The medial femoral approach can reduce damage to blood vessels and muscles, does not interfere with the knee extension device, and does not affect the surgical eld 13,14 . Maintaining the integrity of the knee extension device is bene cial to reduce early pain, promoting knee function recovery, and reducing the length of hospital stay 15,17,19,21,32 . A Meta-analysis by Migliorini et al 33 found that the medial femoral approach was bene cial to reducing blood loss and restoring knee function, and surgeons who have mastered minimally invasive approaches should be encouraged to use minimally invasive approaches for knee replacement, but this analysis failed to distinguish the medial femoral approach from other minimally invasive approaches.…”
Section: Discussionmentioning
confidence: 99%
“…The midvastus(MV) approach can reduce the damage to the blood vessels and muscles, and does not interfere with the knee extension device, which is bene cial for the postoperative quadriceps strength recovery and knee movement and does not affect the surgical eld of vision 13,14 . Nonetheless, whether the MV approach bene ts the recovery of knee function is controversial, focusing on whether it is bene cial for early rehabilitation [15][16][17][18][19][20][21][22] . This study compares the early knee function recovery and patient outcomes following the MV approach and traditional MP approach for halfway tourniquet total knee arthroplasty.…”
Section: Introductionmentioning
confidence: 99%